Revealing a Novel Otubain-Like Enzyme from Leishmania infantum with Deubiquitinating Activity toward K48-Linked Substrate - Azevedo, Clênia S.; Guido, Bruna C.; Pereira, Jhonata L.; Nolasco, Diego O.; Corrêa, Rafael; Magalhães, Kelly G.; Motta, Flávia N.; Santana, Jaime M.; Grellier, Philippe; Bastos, Izabela M. D. (Frontiers in Chemistry, 2017)
Deubiquitinating enzymes (DUBs) play an important role in regulating a variety of eukaryotic processes. In this context, exploring the role of deubiquitination in Leishmania infantum could be a promising alternative to search new therapeutic targets for leishmaniasis. Here we present the first characterization of a DUB from L. infantum, otubain (OtuLi), and its localization within parasite. The recombinant OtuLi (rOtuLi) showed improved activity on lysine 48 (K48)-linked over K63-linked tetra-ubiquitin (Ub) and site-directed mutations on amino acids close to the catalytic site (F82) or involved in Ub interaction (L265 and F182) caused structural changes as shown by molecular dynamics, resulting in a reduction or loss of enzyme activity, respectively. Furthermore, rOtuLi stimulates lipid droplet biogenesis (an inflammatory marker) in peritoneal macrophages and induces IL-6 and TNF-α secretion in peritoneal macrophages, both proinflammatory cytokines. Our findings suggest that OtuLi is a cytoplasmic enzyme with K48-linked substrate specificity that could play a part in proinflammatory response in stimulated murine macrophages.